Blood Feeding Dynamics Of Newly Emerged Cat Fleas, Ctenocephalides Felis (Bouche) (Siphonaptera: Pulicidae) In Chambers Attached To Insecticide-Treated And Untreated Cats - McCoy, Christine M. (Kansas State University, 2006)
The cat flea, Ctenocephalides felis (Bouche) 1835, is an important pest of cats and dogs, yet few studies have been able to document the relatively unhindered feeding dynamic. Studies were conducted to determine the amount of hemoglobin carried over from the larval to adult stage. Next, a series of studies determined flea feeding dynamics within confinement feeding chambers placed on cats. The ratio, total number and gender of fleas determined were then used in a 28-day insecticide study, in which blood consumption per cell was assayed. Fipronil, imidacloprid and selamectin were the topical insecticides evaluated, as well as nitenpyram, a systemic insecticide. The results of this study suggest the importance of the dynamics of flea feeding in relation to the effectiveness of insecticides to reduce feeding.